Loss of PTEN-induced kinase 1 (Pink1) reduces hippocampal tyrosine hydroxylase and impairs learning and memory - Maynard, Mark E. (Exp Neurol, 2019)
Phosphatase and tensin homolog (PTEN)-induced kinase 1 (Pink1) is involved in mitochondrial quality control, which is essential for maintaining energy production and minimizing oxidative damage from dysfunctional/depolarized mitochondria. Pink1 mutations are the second most common cause of autosomal recessive Parkinson’s disease (PD). In addition to characteristic motor impairments, PD patients also commonly exhibit cognitive impairments. As the hippocampus plays a prominent role in cognition, we tested if loss of Pink1 in mice influences learning and memory. While wild-type mice were able to perform a contextual discrimination task, age-matched Pink1 knockout (Pink1(−/−)) mice showed an impaired ability to differentiate between two similar contexts. Similarly, Pink1(−/−) mice performed poorly in a delayed alternation task as compared to age-matched controls. Poor performance in these cognitive tasks was not the result of overt hippocampal pathology. However, a significant reduction in hippocampal tyrosine hydroxylase (TH) protein levels was detected in the Pink1(−/−) mice. This decrease in hippocampal TH levels was also associated with reduced DOPA decarboxylase and dopamine D2 receptor levels, but not post-synaptic dopamine D1 receptor levels. These presynaptic changes appeared to be selective for dopaminergic fibers as hippocampal dopamine beta hydroxylase, choline acetyltransferase, and tryptophan hydroxylase levels were unchanged in Pink1(−/−) mice. Administration of the dopamine D1 receptor agonist SKF38393 to Pink1(−/−) mice was found to improve performance in the context discrimination task. Taken together, our results show that Pink1 loss may alter dopamine signaling in the hippocampus, which could be a contributing mechanism for the observed learning and memory impairments.